Two Photon–Pumped Whispering‐Gallery Mode Lasing and Dynamic Regulation - Lu, Junfeng (Adv Sci (Weinh), 2019)
Realizing the dynamic regulation of nonlinear optical signals has a great scientific significance for the development of new‐type nonlinear optoelectronic devices and expands its application in the field of laser technology, spectroscopy, material structure analysis, etc. Here, two photon absorption–induced whispering‐gallery mode lasing from a single ZnO microresonator with a relatively low lasing threshold (15 µW) and high quality factor (Q ≈ 3200) under ambient conditions is demonstrated. Furthermore, success is achieved in obtaining the dynamic regulation of two photon–pumped lasing mode in the UV gain region. The corresponding resonant wavelength can be tuned dynamically from 388.99 and 391.12 to 390.01 and 392.12 nm for TE(33) and TE(32) modes, respectively. This work provides a new strategy for building high‐performance mode‐adjustable frequency upconversion lasers.